A STUDY OF MARKERS OF IMPORTANCE USED IN LECTURES IN ENGLISH - Đào Thị Linh Tâm (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study is aimed at: - Examining the teachers’ markers of importance in terms of syntactic, semantic and pragmatic features. - Providing the Vietnamese teachers and students of English with an insightful knowledge into the use and interpretation of the meaning of teachers’ markers of importance in lectures in English